The Role of Islamic Values in Sustainable Development Innovation to Support the SDGs in Rural Communities - Al Fajar, Adam Hafidz; Sholichah, Hidayatus; Mudfainna, Mudfainna; Rahma, Rizka Anisa; Agitsna, Izza (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
Sustainable development in rural communities has become a pressing global challenge, particularly in terms of poverty alleviation, reducing inequality, and climate action. Islamic values, through the principles of Maqasid Syariah, offer a relevant approach to achieving these goals. This study aims to explore the application of Maqasid Syariah principles in sustainable development innovations focused on rural communities, as well as to understand the contribution of Islamic values in supporting the achievement of the Sustainable Development Goals (SDGs). The research employs a deductive qualitative method with thematic analysis of data collected through literature review. Data sources include books, journal articles, and official publications related to Maqasid Syariah and sustainable development. The findings show that applying Islamic values, such as social justice, economic protection, and environmental preservation, can significantly support the attainment of the SDGs in rural communities. These findings suggest that Islamic systems like zakat and waqf hold potential for enhancing economic welfare and reducing inequality. This study proposes that integrating Islamic values into development policies can create a more inclusive and sustainable model of development. Thus, it is hoped that religious values serve not only as a spiritual foundation but also as a driving force in achieving holistic and equitable sustainable development for all of humanity.